Unravelling Poverty Indicators in the Tomini Bay Region of Indonesia: A Comprehensive Analysis of SDG 10 - Muhammad Amir Arham; Citra Aditya Kusuma; Ifa Adina Yafiz (Gorontalo State University, 2023)
The Tomini Bay Region, with its abundant natural resources, can be leveraged to promote inclusive and sustainable community welfare in line with SDG 10's global target to reduce inequality. However, despite the region's natural wealth, much of the area is plagued by high poverty. In response, local governments have launched several programs to stimulate economic growth while addressing these issues. To assess the effectiveness of these poverty programs, this study evaluated the economic development of the Tomini Bay area using the SDGs framework. The objectives of this study are twofold: 1) to map the progress of SDG 10 poverty indicators in the region, and 2) to project the achievement of SDG 10 poverty indicator targets in the region by 2030. This study employs quantitative descriptive data analysis. The mapping results are expected to aid local governments in formulating more targeted and inclusive development plans.